Penyelamatan Penanganan Arsip Corona Virus Disease 2019 (Covid-19) pada Dinas Kearsipan dan Perpustakaan Kota Mataram - Rizki Suheldi; Tina Tunnisa; Ida Royani; Abdurrahman Abdurrahman (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The rescue effort of handling the archives of the Coronavirus Disease 2019 (COVID-19) pandemic at the Archives and Library Office of Mataram City aims to document and preserve information related to the COVID-19 pandemic in Mataram City. The rescue effort is carried out by identifying, collecting, processing, and storing COVID-19 archives in physical and digital forms. These archives include policy documents, statistical data, activity reports, and other documentation related to handling COVID-19 in Mataram City. This is crucial for several reasons. First, these archives have high historical value and can be used to study how Mataram City handled the COVID-19 pandemic. Second, these archives serve as research materials for developing future disaster management policies and strategies. Third, these archives serve as evidence of government accountability and transparency in handling the COVID-19 pandemic. The archive rescue effort at the Archives and Library Office of Mataram City is still in its early stages. However, this effort demonstrates the commitment of the Mataram City government to document and preserve information related to the COVID-19 pandemic. This rescue effort by the village community institution in Mataram City is an important step in preserving valuable information related to the Covid-19 pandemic.